To the bicentennial: republic in extinction ?: a necessary debate - Mendívil Nina, José (2019)
I maintain that the extinction of our republic is taking place, and that the problem we will have in the world that is coming will be that of the definitive death of the promise of Peruvian life of which Basadre spoke to us; extinction that seems to have been destined for its fulfillment in the XXII century if we continue to be a republic accustomed to losing ourselves daily in the evils of corruption and authoritarianism, of illegality and misgovernment, of cultural backwardness and social marginality, of anomie and transient rebellion, ignorance and mediocrity, as if it only existed to withstand defeats and failures, ridicule and ridicule, easy promises and repeated deceptions, and would have been founded for the inevitable loss of opportunities that its future offers.